Investigating the Role of Helmet Layers in Reducing the Stress Applied During Head Injury Using FEM - Gholampour, Seifollah; Hajirayat, Keyvan; Erfanian, Armin; Zali, Ali Reza; Shakouri, Ehsan (International Clinical Neuroscience Journal, 2017)
Background: Motorcycle accidents and sport accidents lead yearly to many head injuries like head fractures and concussion. So finding the most proper helmet for reducing the injuries to head can be very helpful for head protection in such cases. Methods: After 3D modeling of the helmet and head and meshing the model, a compressive impacting load of 1.31MPa was exerted on head and the model was analyzed using FEM. The helmet was considered as a two-layered helmet composing of an inner and an outer layer. Skull and CSF were considered as external layers of head. The analysis was repeated for a helmet with an inner layer made of extruded polystyrene (XPS), a helmet with an inner layer of expanded polystyrene (EPS) and finally a helmet with two internal layers of XPS and EPS. Results: The amounts of maximum displacement of the outer layer in the helmet with a XPS inner layer, the helmet with an EPS inner layer and the helmet with two internal layers were 2.82, 3.15 and 2.98mm, respectively and the respective amounts of stress were 32.05, 43.38 and 34.3MPa. The amounts of maximum stress in the inner and outer layer of the helmet with a XPS inner layer were respectively 16.4% and 6.6% less than those in the helmet with two internal layers. Discussion: Since the helmet with a XPS inner layer reduces the stress more than the helmet with two internal layers, it is the most optimal model for mitigating the head injury due to an impacting load. It should be noted that for simplifying the models, the dura was modeled together with the skull and the thicknesses of the XPS and EPS foam layers were considered to be equal.